Multiple endocrine neoplasia type 1 in a patient diagnosed with nesidioblastosis. A case presentation - Olivia Elizabeth Altamirano Guerrero; María Gabriela Balarezo García; Juan Sebastián Lima Icaza (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Multiple endocrine neoplasias encompass a series of syndromes characterized by their genetic origin and the involvement of one or more glands. A 23-years-old male patient with a health history of nesidioblastosis diagnosed at 16 years of age, who attended the Ambato General Teaching Hospital with tonic-clonic seizures and severe hypoglycemia with subsequent epileptic status, is described. Laboratory studies showed primary hyperparathyroidism, and imaging identified lesions suggestive of parathyroid adenoma and insulinoma of the head of the pancreas. After analyzing the case, two criteria were identified to suggest multiple endocrine neoplasia type 1: presence of insulinoma and primary hyperparathyroidism. In addition to treatment with bisphosphonate, consultation with the Genetics service was planned for study of the patient and family members; and with General Surgery, for scheduling surgical resolution. Due to the infrequency of this disease, it is of interest to describe the case, with the aim of exposing the main clinical manifestations and conduct to follow. Diagnosing its cause in each patient is a priority.